Enhanced hemato-endothelial specification during human embryonic differentiation through developmental cooperation between AF4-MLL and MLL-AF4 fusions - Bueno, Clara (Haematologica, 2019)
The t(4;11)(q21;q23) translocation is associated with high-risk infant pro-B-cell acute lymphoblastic leukemia and arises prenatally during embryonic/fetal hematopoiesis. The developmental/pathogenic contribution of the t(4;11)-resulting MLL-AF4 (MA4) and AF4-MLL (A4M) fusions remains unclear; MA4 is always expressed in patients with t(4;11)(+) B-cell acute lymphoblastic leukemia, but the reciprocal fusion A4M is expressed in only half of the patients. Because prenatal leukemogenesis manifests as impaired early hematopoietic differentiation, we took advantage of well-established human embryonic stem cell-based hematopoietic differentiation models to study whether the A4M fusion cooperates with MA4 during early human hematopoietic development. Co-expression of A4M and MA4 strongly promoted the emergence of hemato-endothelial precursors, both endothelial- and hemogenic-primed. Double fusion-expressing hemato-endothelial precursors specified into significantly higher numbers of both hematopoietic and endothelial-committed cells, irrespective of the differentiation protocol used and without hijacking survival/proliferation. Functional analysis of differentially expressed genes and differentially enriched H3K79me3 genomic regions by RNA-sequencing and H3K79me3 chromatin immunoprecipitation-sequencing, respectively, confirmed a hematopoietic/endothelial cell differentiation signature in double fusion-expressing hemato-endothelial precursors. Importantly, chromatin immunoprecipitation-sequencing analysis revealed a significant enrichment of H3K79 methylated regions specifically associated with HOX-A cluster genes in double fusion-expressing differentiating hematopoietic cells. Overall, these results establish a functional and molecular cooperation between MA4 and A4M fusions during human hematopoietic development.